Tantangan dan Peluang dalam Pengembangan Profesionalisme Guru di Era Digital: Suatu Kajian Literatur - Ferry Lourens Sampel Korompis; Stany Rawung; Dominikus Rojoki Manullang; Sahat Renol HS (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
The development of digital technology has driven significant changes in education and requires teachers to adapt to new learning paradigms. Teachers are expected to possess professional competencies, including pedagogical skills, content mastery, digital literacy, and readiness for technological transformation. This study aims to analyze the challenges and opportunities for developing teacher professionalism in the digital era through a literature review. The data were obtained from 35 scientific articles written in Indonesian and published in national journals, accessed through Google Scholar between 2020 and 2025. The findings indicate several challenges, such as digital literacy gaps, limited technological infrastructure, resistance to change, lack of continuous training, and high administrative workloads. However, the digital era also offers opportunities for teachers to enhance competencies through online learning platforms, digital media innovation, data-based assessment, and supportive government policies. Developing teacher professionalism requires collaboration among teachers, educational institutions, and policymakers to build an innovative and sustainable learning ecosystem. Adaptive teachers can become agents of change in achieving quality education.